2022
DOI: 10.1108/ijotb-05-2021-0082
|View full text |Cite
|
Sign up to set email alerts
|

Participative climate, team job crafting and leaders' job crafting: a moderated mediation model of team performance

Abstract: PurposeDespite increasing interest in team performance, particularly in team-based work environment, the literature is underdeveloped in explaining the mechanisms that lead to team performance. The purpose of this paper, a team-level research, is to advance the understanding of one of the mechanisms that explains how participative climate relates to team performance by studying the roles of team job crafting and leader job crafting in the process.Design/methodology/approachA moderated mediation model of team p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…Oldham & Hackman (2010) define job crafting as changes that occur on one's own initiative while performing tasks based on needs and resources, with or without management intervention, through activities such as designing, creating, reviewing, and modifying (Khan et al 2022). Both of these opinions support the theory by Wrzesniewski & Dutton (2001) that job crafting is a contextual activity that can enable or disable different situations across various levels and types of jobs.…”
Section: ______757mentioning
confidence: 99%
See 1 more Smart Citation
“…Oldham & Hackman (2010) define job crafting as changes that occur on one's own initiative while performing tasks based on needs and resources, with or without management intervention, through activities such as designing, creating, reviewing, and modifying (Khan et al 2022). Both of these opinions support the theory by Wrzesniewski & Dutton (2001) that job crafting is a contextual activity that can enable or disable different situations across various levels and types of jobs.…”
Section: ______757mentioning
confidence: 99%
“…It is demonstrated that each employee is provided with a uniform understanding according to their duties and functions. With higher participation, tasks can be carried out collectively, which in turn will result in team performance (Khan et al 2022). Active involvement in the structure of work processes like this is a form of employee commitment to the organization.…”
Section: ______mentioning
confidence: 99%
“…One of the behaviors that employees must have is job crafting. According to Guan and Frenkel (2018), Zhang and Liu (2021), Nguyen et al (2019), and Moon et al (2020), job crafting can affect employee performance because employees will carry out a behavior change process to adapt to job characteristics (Dan et al, 2020;Khan et al, 2022;Li et al, 2022). Its effectiveness can improve work and help individuals maintain employee engagement (vigor, absorption, and dedication) (Liu et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The adaptive performance comprises change-receptive behaviors, where individuals act energetically towards unforeseen challenges. Predicting the unanticipated is a challenging task requiring learning-oriented behaviors to cope with technological shifts, particularly in dynamic and agile industries like the software development industry (Khan et al, 2022). Consequently, adaptive performance involves managing crises and emergencies, handling unpredictable work situations, reducing work-related stress, finding creative solutions, learning new work tasks and technologies and displaying interpersonal and cultural adaptability (Griffin and Hesketh, 2003).…”
Section: Introductionmentioning
confidence: 99%